JILBAB SEBAGAI GAYA HIDUP WANITA MODERN DI KALANGAN MAHASISWI FAKULTAS ILMU SOSIAL DAN POLITIK UNIVERSITAS SAM RATULANGI - Mahmud, Yulcin; Paat, Cornelius J.; Lesawengen, Lisbeth (Universitas Sam Ratulangi, 2020)
Jilbab is a loose clothes brackets that are equipped with a veil that covers the head, part of the face and chest. The veil illustrates the obedience of a Muslim woman to the teachings of Islam, because Islam does require women to cover their genitals, and the veil is one of the genitalia covering the head to the chest of women. In social life, some people consider that a Muslim woman who wears the hijab should be able to maintain her behavior and language in order to remain good and polite as should the sanctity of a veil she wears.After the hijab as a lifestyle of modern women among female students, the reason female college students do to wear the hijab is because it can protect them from the sun and rain. Besides wearing the hijab protect from adultery. The impact of the hijab that occurred is positive and negative impacts. The positive is that many female students today choose to use the veil in every activity and there are also negative impacts, namely the headscarves that are still visible, some are visible to the ears, and others that are certainly not shar'i.With the hijab as a lifestyle of modern women, many students want to wear the hijab because the hijab model is now more modern, varied and simple. The hijab is most commonly used during formal activities such as going to college, traveling and working.Keywords : Hijab, Lifestyle, Student